A phenomenological study of female dance majors from single-parent families after psychological counseling by a counselor - Chen, Shuo; Zuo, Jing (Frontiers in Psychology, 2025)
IntroductionSingle-parent families have recently become more common attributable to the increasing divorce rates in China. This has increased the prevalence of major psychological problems. Chinese tertiary students express their personal and developmental needs to school counselors as the key personnel in universities. Counselors provide standard social guidance to help with their psychological development and improvement. Herein, we conducted qualitative research with five female dance majors from single-parent families through in-depth interviews. Specifically, we sought to explore the impact of psychological counseling by counselors on the well-being of college students from single-parent families.MethodThis qualitative research was primarily based on in-depth interviews for five female dance majors from single-parent families.ResultsEleven meaning units were identified, which were organized into five themes and two fundamental aspects, capturing the psychological counseling experiences of participants with their counselors. The five themes included interpersonal relationship concerns, personal internal issues, external symptoms of issues, changes in interpersonal relationships and internal issues, and persistence of personal habits. Furthermore, the counseling experience was largely defined by changes in individuals’ internal struggles and their external behaviors.DiscussionOur findings highlight the significance of psychological counseling counselors, the psychological problems affecting female college students from single-parent families, and the need for long-term interventions, given the persistent nature of personal habits such populations develop over time. Although this study did not specifically explore the psychological problems of students from single-parent families, it offers practical insights, which could guide future research in the realm of psychological counseling of such populations.